Unveiling Limestone Orchid Hotspots in the Karst Hills of Northern Peninsular Malaysia - Shahrul Nizam, Abu Bakar; Farhan, Rashid; Muhammad Hilmi, Jamaluddin; Muhamad Faizal, Md Azmi; Ahmad Sofiman, Othman; Rahmad, Zakaria; Azimah, Azimah Abd Rahman; Mohd Akmal, Mohd Raffi; Farah Alia, Nordin (MDPI, 2023)
To date, documentation of the diversity of orchids from the limestone hills in the northern part of Peninsular Malaysia, particularly in the states of Kedah and Perak, is still lacking, with limited literature available. There is indeed an urgent need to fill this knowledge gap, so that proper documentation of the diversity of orchids from this unique karst habitat can be prepared. In this study, a series of 12 months of diversity assessments on five limestone hills in Kedah and Perak has resulted in the discovery of 56 orchid species from 37 genera. From this account, 12 species are new records within Kedah and 2 species are new records within Malaysia, namely Bulbophyllum meson J.J.Verm., Schuit. & de Vogel and Luisia brachystachys (Lindl.) Blume. Three species are endemic to Peninsular Malaysia which are Anoectochilus sanguineus P.T.Ong & P.O’Byrne, Cheirostylis goldschmidtiana Schltr. and Phalaenopsis appendiculata Carr. Findings of two keystone species, the long-lost Cheirostylis goldschmidtiana and the endangered snow-white slipper orchid, Paphiopedilum niveum (Rchb.f.) Stein, have catalyzed the need for a more comprehensive study to unveil the species richness and endemism within a limestone habitat. Heat maps using geographical data produced from ArcGIS software have enabled precise determination of the areas with the highest concentration of orchid diversity. Results from this study have shown that Gunung Fakir Terbang houses the greatest number of orchid species, followed by Gunung Batu Putih and Gunung Baling. Meanwhile, lower species occurrences were recorded from Gunung Pulai and Gunung Pong. However, lack of attention and delayed conservation action on this unique karst habitat would only lead to more habitat loss, leading to the decline of limestone orchid populations. Orchids as well as other plants are threatened by anthropogenic activity such as quarrying and forest clearing for agriculture. Thus, the results of this study will serve as baseline data for future work in documenting and conserving limestone orchids and their karst habitat in northern Peninsular Malaysia.